2020
DOI: 10.4103/jfmpc.jfmpc_765_20
|View full text |Cite
|
Sign up to set email alerts
|

Self-perception on oral health and related behaviours among antenatal mothers attending a public antenatal clinic – Kerala

Abstract: Background and Aims: Antenatal oral care has been given least priority on a global scale. The study assesses self-perception of oral health knowledge and related behaviors among antenatal mothers. Method: A cross-sectional study was done among 400 pregnant women attending antenatal care clinic of a tertiary care center in Kerala, India. Details regarding knowledge, attitude, and practice were obtained, after getting an informed consent. The dental caries experience and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Systematic reviews have found that pregnant women had poor knowledge and awareness of oral health [ 35 , 36 ]. Bindu et al [ 37 ] also found that pregnant women placed lower priority for oral and fear for dental services were reasons for delaying dental services. Also, higher parity has been associated with number teeth present, functional tooth units of natural teeth regardless of socio-demographic and behavioural variables [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Systematic reviews have found that pregnant women had poor knowledge and awareness of oral health [ 35 , 36 ]. Bindu et al [ 37 ] also found that pregnant women placed lower priority for oral and fear for dental services were reasons for delaying dental services. Also, higher parity has been associated with number teeth present, functional tooth units of natural teeth regardless of socio-demographic and behavioural variables [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The lack of awareness regarding priority status and cost of treatment in pregnant women was evident in both GPs and patients. 2,5,9 In accordance with the DHSV priority population guidelines, pregnant women holding a governmentfunded concession (Health Care Card or Pension Card) are eligible for public dental care, hence, those birthing at the hospital were screened for concession prior to referral. One-third of antenatal women were eligible in the post-intervention period.…”
Section: Discussionmentioning
confidence: 99%
“…Physical and hormonal changes occur during pregnancy that predisposes women to an increased risk of oral diseases. 2,[6][7][8][9][10] Research has shown that it is important to monitor and maintain oral hygiene during pregnancy. 1,3 Evidence shows that up to two-thirds of pregnant women can experience periodontal disease.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations